The role of family ownership on internationalization strategies - Joana Costa; Jo\~ao Barbosa (Administrative Sciences, 2024)
The present study examines the impact of family ownership and control on the internationalization strategies of Portuguese manufacturing firms. The study contributes to the existing literature by providing evidence that different forms of international market presence are asymmetrically influenced by family control and by underscoring the importance of innovative strategies. The analysis includes a sample of 25,533 firms observed from 2018 to 2021. Econometric models address the role of ownership in alternative internationalization endeavors, demonstrating that these firms differ from their non-family counterparts. By comparing the export propensity, intensity, and reach of family businesses to non-family businesses, the research sheds light on the challenges faced by family-owned firms and the significance of structural characteristics such as technological regimes and regional competitive advantages. The findings emphasize the negative impact of family presence on internationalization while highlighting the importance of innovation and ecosystem support. Additionally, the study contributes to the empirical refinement of firm classification by proposing a more reliable segmentation method. It also presents alternative econometric methods to appraise internationalization strategies better. Future research directions are suggested, particularly regarding the use of additional information related to innovation and human capital, offering insights for enhancing the global engagement of family businesses in global markets. This research provides valuable empirical evidence and practical implications for policymakers and practitioners seeking to support the required actions to promote the growth and internationalization of family businesses in the context of the Portuguese manufacturing industry.
Keywords: 350; export intensity; export propensity; family business; internationalization; multinomial logit; tobit